Physicochemical quality indicators of honey: An evaluation in a Ukrainian socioecological gradient - A. Zhuk; I. Sytnikova; T. Fylypchuk; O. Bahlei; O. Shkrobanets; J. Danihlík; H. Moskalyk; I. Panchuk; V. Burkut; P. Angelstam; M. Fedoriak (Regulatory Mechanisms in Biosystems, 2022)
Physical and chemical quality indicators of 65 polyfloral honey samples from three administrative districts of Chernivtsi region in South Western Ukraine were studied. The chosen administrative districts were Putyla (representing the ‘Traditional villages’ stratum), Storozhynets (the ‘Intermediate’ stratum) and Khotyn (the ‘Intensive agriculture’ stratum), which reflect a steep gradient of social and ecological conditions such as land cover and land use, level of economic development, culture and demography. The quality of honey was determined in accordance with the requirements of the Ukrainian national standard and the EU Directive relating to honey (or Codex Alimentarius Honey Standard) by using the following indicators: reducing sugars and moisture content, diastase activity, free acidity, pH, electrical conductivity, hydroxymethylfurfural (HMF) and proline content. The profile of carbohydrates was analyzed, in particular glucose, fructose, sucrose, maltose, trehalose, melezitose, raffinose. The ratio of fructose to glucose (F/G) was determined. All tested samples complied with the international standards for the mass fraction of reducing sugars, diastase activity and hydroxymethylfurfural content. For physical and chemical parameters, the studied honey samples were of high quality. The content of the reducing sugars in the honey samples varied within the range of 66.0–97.6%. The fructose content ranged from 342 to 549 mg/g, and the glucose content variation ranged within 283–517 mg/g. The average fructose/glucose ratio was 1.2 for honey samples from the three studied districts. Besides fructose and glucose, some oligosaccharides, such as maltose, trehalose and melezitose, were found in the examined honey. Melezitose was detected in the honey samples from ‘Traditional village’ (21 samples) and ‘Intermediate’ (5 samples) districts. The total variability of HMF content in the studied 65 honey samples from apiaries in the three districts of Chernivtsi region ranged from 0.19 to 30.8 mg/kg. The minimum moisture content was found to be 16.2% (in the ‘Traditional village’ and ‘Intermediate’ strata), and 22.2% was the maximum (in the ‘Intermediate’ stratum). Our studies have shown that free acidity of the samples varied within the range 13.5 to 58.0 meq/kg. Proline content variability for the three studied geographical areas ranged from 82.3 to 1201.2 mg/kg. The studied samples of honey had a low pH level (~ 3.7), high content of proline (~ 513 mg/kg) and reducing sugars (~ 80%), which indicates its nutritional value and naturalness. Deviations from the honey standards in moisture content, acidity and electrical conductivity was revealed in 8% to 10% of all samples.